2019
DOI: 10.4274/tjod.galenos.2018.89663
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of Rubella in pregnant women in Turkey: a meta-analysis research of 90988 Rubella IgM, 84398 Rubella IgG, and 522 avidity results

Abstract: Objective: Rubella infection prevalence in pregnant women can vary from country to country, or even across regions in the same country. In this metaanalysis, the seroprevalence Rubella among pregnant women in Turkey in the last decade was evaluated. Materials and Methods: Studies conducted in Turkey between 2007 and 2017 were analyzed, and differences in seroprevalence between provinces were compared by evaluating Rubella immunoglobulin (Ig)-G, IgM, and IgG avidity resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…WHO estimates show that this ratio is 45% in Turkey (14). Rubella IgG and IgM it has been demonstrated rates were 94.87% and 0.783%, respectively for pregnant woman in the meta-analysis study in Turkey (15). A recent study in Turkey shows that seropositivity for anti-rubella IgG and IgM were 89 and 0.19%, respectively (16).…”
Section: Discussionmentioning
confidence: 89%
“…WHO estimates show that this ratio is 45% in Turkey (14). Rubella IgG and IgM it has been demonstrated rates were 94.87% and 0.783%, respectively for pregnant woman in the meta-analysis study in Turkey (15). A recent study in Turkey shows that seropositivity for anti-rubella IgG and IgM were 89 and 0.19%, respectively (16).…”
Section: Discussionmentioning
confidence: 89%
“…! from different areas of Turkey showed that the rate of susceptibility to rubella in native pregnant women ranged from 2.5% to 17%, and IgG seropositivity ranged from 83.69 to 97.5% [16][17][18]. There is a limited number of studies conducted on Syrian refugees in Turkey for the susceptibility of rubella, and according to one of these studies, which had results that were similar to this study, 1333 Syrian pregnant woman were evaluated, and the IgG seropositivity was found to be 92.8% [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizde yakın zamanlı yapılan bir metaanaliz çalışmasında, anti-rubella virus IgG ve IgM pozitiflik oranları sırası ile %91-95 ve %0.5-1.1 olarak belirlenmiştir (36) . Çalışmamızda, hastanemize başvuran gebelerde anti-rubella virus IgG pozitiflik oranını %87.…”
Section: Gereç Veunclassified